Infective endocarditis due to Bartonella bacilliformis associated with systemic vasculitis: a case report - Peñafiel-Sam,Joshua (2017)
Abstract Infective endocarditis due to Bartonella bacilliformis is rare. A 64-year-old woman, without previous heart disease, presented with 6 weeks of fever, myalgias, and arthralgias. A systolic murmur was heard on the tricuspid area upon examination, and an echocardiogram showed endocardial lesions in the right atrium. Bartonella bacilliformis was isolated in blood cultures, defining the diagnosis of infective endocarditis using Duke’s criteria. Subsequently, the patient developed clinical and laboratory features compatible with antineutrophil cytoplasmic antibody-associated vasculitis. This case presents an uncommon complication of B. bacilliformis infection associated with the development of systemic vasculitis.